Law and global health - Freeman, Michael D. A.; Hawkes, Sarah; Bennett, Belinda (Oxford : Oxford University Press, 2014)
'Law and Global Health' is the latest volume in the 'Current Legal Issues' series. It contains a broad range of articles from scholars and public health experts discussing the interaction between law and public health in low-, and middle- and high-income countries.
Description based on online resource; title from home page (viewed on July 8, 2014).
Keywords: Public health laws; World health; Public health laws, International